Employee Training and Power Distance: A Case of Employees in Private Higher Education Institutions in Kuala Lumpur - Nor Asyrin, Baharudin (2012)
Training is an important function of human resource management. However, prior research about the relation between employee training and power distance mostly focuses on private higher education institutional within Kuala Lumpur, uses a few single case studies or examines only power distance. To address this need, the researcher will provide a theoretical framework which proposes that power distance factors affect training methods and training motivation. Data was gathered through distributed questionnaires answered by 300 respondents from employees in higher education institutional within Kuala Lumpur. Data was analyzed using the Statistical Package for Social Sciences (SPSS v.16) where descriptive analysis was used to analyze the social demographic variable of the respondent; and the Pearson Correlation Analysis was used to analyze the level of significant relationship between training methods with power distance and training motivation with power distance. Implications for practice and future research are discussed.